miR-155 Is a Positive Regulator of FcεRI-Induced Cyclooxygenase-2 Expression and Cytokine Production in Mast Cells - Mohammed, Zahraa; McHale, Cody; Kubinak, Jason L.; Dryer, Stuart; Gomez, Gregorio (Frontiers in Allergy, 2022)
MicroRNA-155 (miR-155) has been implicated in IgE-dependent allergic disease including asthma and atopic dermatitis. A few roles for miR-155 have been described in mast cells and some specifically related to IgE receptor signaling, but it is not completely understood. Here, we demonstrate by miRNA seq profiling and quantitative RT-PCR that miR-155 expression is significantly increased in human skin-derived mast cells (SMCs) and mouse bone marrow-derived mast cells (BMMCs) following FcεRI crosslinking with antigen. We demonstrate that FcεRI-induced expression of cyclooxygenase-2 (COX-2) was significantly inhibited in miR-155 knockout (KO) BMMCs whereas arachidonate-5-lipoxygenase (ALOX-5) expression and leukotriene C4 (LTC4) biosynthesis, and degranulation were unaffected. FcεRI-induced cytokine production (TNF, IL-6, and IL-13) from miR-155 KO BMMCs was also significantly diminished. Correspondingly, Akt phosphorylation, but not protein expression, was inhibited in the absence of miR-155 whereas p38 and p42/44 were unaffected. Interesting, lipopolysaccharide (LPS)-induced cytokine production was increased in miR-155 KO BMMCs. Together, these data demonstrate that miR-155 specifically targets the FcεRI-induced prostaglandin and cytokine pathways, but not the leukotriene or degranulation pathways, in mast cells. The data further suggest that miR-155 acts indirectly by targeting a repressor of COX-2 expression and a phosphatase that normally blocks Akt phosphorylation. Overall, this study reveals the role of miR-155 as a positive regulator of mast cell function.